A transcription and textual analysis of Mehmed Memduh Pasha’s Eser-i Memdûh as a comparison of pen and sword - Şahin, Muhammed. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2021., 2021)
This study consists of a transcription of the Eser-i Memdûh written in the nineteenth century by Mehmed Memduh Pasha, and includes research on both the text and its writer. Eser-i Memdûh, which consists of forty five pages, is a prose work that was written in the “inşa” style, and includes verse parts. Its subject regards the comparison between pen and sword. The text has been examined with regard to style and content and it is aimed to make it accessible by transcription. The first chapter introduces the author, Mehmed Memduh Pasha, and explains the relationship of Eser-i Memdûh with the genre of debate. The second chapter discusses the development of pen and sword narratives and clarifies the characteristics of the “inşa” style and the effect of Encümen-i Şuarâ, of which the author was a member, by means of the text. The third chapter states the method in the preparation of the text, transcription system and concludes with a transcription of the text. This study is significant in terms of transferring Eser-i Memdûh, which stands out with its language features and wording peculiar to the seventeenth century, although it was written in the nineteenth century, to the Latin alphabet for the first time, and a contribution to the Encümen-i Şuarâ studies.